Considerations about prescribed work: reflections on modalizations which focus on teachers’ acting - Souza, José Wellisten Abreu (2015)
In this article we have the aim to analyze the educational work represented in texts which (re)shape the work of Portuguese language teachers in terms of prescribed work. Therefore we intended to make a detailed review of the following sections of the National Curricular Parameters (PCN): “Learning and  Teaching  Portuguese  Language  in  schools”, “Considerations  related  to didactic treatment of content” and the subsections which focused the “Didatic Treatment”.  Our  analysis  focuses  on  modalizations  referring  to  the  work of  the  teacher,  as  suggested  by  Bronckart  in  the  theoretical  framework  of Sociodiscursive Interactionism (SDI).